2014
DOI: 10.1002/aqc.2445
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing residual reserves in the sea: are we favouring ease of establishment over need for protection?

Abstract: ABSTRACT1. As systems of marine protected areas (MPAs) expand globally, there is a risk that new MPAs will be biased toward places that are remote or unpromising for extractive activities, and hence follow the trend of terrestrial protected areas in being 'residual' to commercial uses. Such locations typically provide little protection to the species and ecosystems that are most exposed to threatening processes.2. There are strong political motivations to establish residual reserves that minimize costs and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
375
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(382 citation statements)
references
References 95 publications
3
375
0
4
Order By: Relevance
“…Several studies (e.g., refs. 42-44) have shown that the global network of protected areas is ineffective and is biased toward residual locations; these places are considered cheap to protect because they are remote or of low economic value, making it easier to set them aside for protection (7,44,45). Our findings combined with these other studies at local and regional scales demonstrate that currently protected areas are not maximizing the coverage of biodiversity.…”
Section: Resultsmentioning
confidence: 53%
“…Several studies (e.g., refs. 42-44) have shown that the global network of protected areas is ineffective and is biased toward residual locations; these places are considered cheap to protect because they are remote or of low economic value, making it easier to set them aside for protection (7,44,45). Our findings combined with these other studies at local and regional scales demonstrate that currently protected areas are not maximizing the coverage of biodiversity.…”
Section: Resultsmentioning
confidence: 53%
“…Most conservation approaches aim to identify and protect places of high ecological integrity under minimal threat 8 . Yet, with escalating social and environmental drivers of change, conservation actions are also needed where people and nature coexist, especially where human impacts are already severe 9 .…”
Section: Main Textmentioning
confidence: 99%
“…Regimes agroambientais/conservação e gestão ambiental Devillers et al (2015) Reinventing residual reserves in the sea: Are we favouring ease of establishment over need for protection?…”
Section: Autoria/anomentioning
confidence: 99%